The role of physical activity in modulating six-minute walk distance in adolescents - Attilio Carraro; Roberto Roklicer; Giampaolo Santi; Alessandra Colangelo; Marco Petrini; Marta Duina; Markus Gerber; Antonino Mulè (PLoS ONE, 2026)
Purpose The six-minute walk test (6MWT) is one of the most widely utilized submaximal tests to assess cardiorespiratory fitness in both healthy and clinical populations. The present study aims to provide 6MWT reference values for Italian adolescents (11–18 years) and to identify key variables influencing the six-minute walk distance (6MWD). Methods Data were collected from 3276 Italian adolescents (48% males). Participants provided self-reported age, height, weight, and weekly practice of moderate-to-vigorous physical activity (MVPA). 6MWT was performed to assess participants’ cardiorespiratory fitness. Results Average distances of 730.0 (IQR: 674.0–788.0) and 675.0 (IQR: 624.0–720.0) meters were walked in the 6MWT by male and female adolescents, respectively. Multiple linear regression models, used to investigate whether demographics, anthropometrics, and MVPA predicted the 6MWD, revealed statistically significant results in both males ( p < .001, F = 28.94, adjusted R 2 = 0.11) and females ( p < .001, F = 23.00, adjusted R 2 = 0.09). In male adolescents, MVPA and age positively predicted the 6MWD, whereas BMI negatively predicted the 6MWD. In female adolescents, MVPA positively predicted 6MWD, whereas age and BMI negatively predicted 6MWD. No interaction effects were found. Conclusion The reference percentiles of distance walked, classified by sex and age, reported in the present study can be used as a practical tool to assess adolescents’ cardiorespiratory fitness. This study also highlights the importance of PA engagement in this population, as it was considerably associated with the average distance walked. Consequently, in addition to anthropometric and demographic variables, future studies should pay particular attention to the amount of MVPA practiced.